Ethnic Identity Construction and Contestation in Bangladesh: The Case of the Manipuri and Bishnupriya Communities - Rajmoni Singha (Journal of Asian Social Science Research, 2024)
In Bangladesh, some groups seek economic or social advantages by claiming ethnic identities to which they are not entitled. This paper examines such claims, focusing on the identity challenges faced by the Manipuri community due to competing claims from the Bishnupriya. Despite clear distinctions in linguistic, historical, and cultural origins, as recognized in the literature, the Bishnupriya community asserts a Manipuri identity, creating tensions and contestations. The Manipuri, known as Meetei locally and internationally, are one of the recognized ethnic groups in Bangladesh. However, their identity is increasingly contested by the Bishnupriya, whose claims lack alignment with established definitions of Manipuri ethnicity. Although this issue is significant for the Manipuri community, it remains underexplored in Bangladeshi scholarship. This study addresses the gap using qualitative methods, including in-depth interviews and participatory observations, complemented by secondary sources and scholarly research. The findings highlight the complexity of ethnic identity construction and its implications for minority communities in Bangladesh.